2009
DOI: 10.1111/j.1467-9353.2009.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

The Productivity Effects of Extension Appointments in Land-Grant Colleges

Abstract: This article analyzes the primary activities of agricultural college faculty with and without extension appointments using survey data. The evidence suggests that differences between extension professors and others in agricultural colleges in terms of research production are small for minor extension appointments, but show significant and increasing trade-offs between extension and research outputs above a 40% extension appointment. The evidence is broadly suggestive of the potential for gains from exploiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Our faculty perceptions of public engagement might have otherwise been skewed by the inclusion of extension faculty since they may experience different motivations and barriers than non-extension faculty. In fact, previous research shows that having an extension appointment is positively associated with more frequent participation in public engagement activities [ 42 ]. Excluding extension faculty allowed us to focus on perspectives from faculty who are not formally expected to engage with the public based on their appointment, but rather must choose to engage with the public on their own accord.…”
Section: Methodsmentioning
confidence: 99%
“…Our faculty perceptions of public engagement might have otherwise been skewed by the inclusion of extension faculty since they may experience different motivations and barriers than non-extension faculty. In fact, previous research shows that having an extension appointment is positively associated with more frequent participation in public engagement activities [ 42 ]. Excluding extension faculty allowed us to focus on perspectives from faculty who are not formally expected to engage with the public based on their appointment, but rather must choose to engage with the public on their own accord.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, female scientists are somewhat less willing to engage through the media than their male counterparts, though the gender differences in participating in some other activities are small (Besley et al, 2018). Having an extension appointment was also controlled for because public engagement is heavily weighted and explicitly incentivized for those with extension appointments (e.g., Foltz & Barham, 2009). Finally, research fields can influence the type of engagement activities that scientists participate in.…”
Section: Methodsmentioning
confidence: 99%
“…As such, it is expected that faculty with extension appointments regularly engage and collaborate with multiple stakeholders, necessitating the development of skills to effectively engage with these stakeholders and the public, more broadly. Research on the impact of extension appointments on engagement participation showed that holding an extension appointment above 40% drastically increased the number of extension clientele presentations a researcher had with stakeholders (Foltz and Barham, 2009). Therefore, extension appointments represent an active, institutionalized form of public engagement.…”
Section: Government Funding and University Extension Systemmentioning
confidence: 99%